The repair of DNA breaks in Escherichia coli and analysis of the bacterial recombination protein RecN - Wood, Stuart Robert (2009)
A DNA double-strand break is an exceptionally toxic lesion that threatens the structural and functional integrity of the genome. In this thesis the repair of DSBs was investigated using the bacterium Escherichia coli, which repairs DNA breaks almost exclusively by homologous recombination. The studies described focus on the repair of damage induced by reactive oxygen species, but especially on the RecN protein, which is associated specifically with the repair of double-strand breaks.